2019
DOI: 10.4103/jlp.jlp_27_19
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of in vitro susceptibility of fosfomycin among Enterobacteriaceae isolates from urine cultures: A study from Puducherry

Abstract: INTRODUCTION: The increasing drug resistance among Gram-negative uropathogens and a lack of effective oral antibiotics have limited the therapeutic options available for urinary tract infections (UTIs). This shortage of newer antibiotics has paved the way for considering the use of older antibiotics such as fosfomycin. This study aims to evaluate the in vitro susceptibility of Enterobacteriaceae isolates to fosfomycin. MATERIALS AND METHODS: In this descriptive study conducted over a period of 6 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…With gentamicin, the resistance did not exceed 5.4% with E. coli and 10.1% with K. pneumoniae. However, this molecule showed a high resistance rate of 52.3% and 68% against uropathogenic enterobacterial isolates in an Indian and Ethiopian study, respectively [48,49].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…With gentamicin, the resistance did not exceed 5.4% with E. coli and 10.1% with K. pneumoniae. However, this molecule showed a high resistance rate of 52.3% and 68% against uropathogenic enterobacterial isolates in an Indian and Ethiopian study, respectively [48,49].…”
Section: Discussionmentioning
confidence: 93%
“…We mention the use of other molecules such as the pipiracillin-tazobactam combination [53]. Another study suggested that fosfomycin and nitrofurantoin could be an excellent therapeutic option for UTIs [20,49,54]. In Morocco, fosfomycin has shown promising in vitro activity against multidrug-resistant urinary tract infections [24].…”
Section: Discussionmentioning
confidence: 99%
“…Another study done by Wali et al in their study 24 Enterococcus species were isolated. 20 isolates (80%) of enterococcal species showed to be sensitive to nitrofurantoin 27 . A study Ali, Shamshad, et al, they isolated 100 Enterococcus species where 81 isolates (81%) showed to be sensitive to nitrofurantoin 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in India have reported around 95% sensitivity for Fosfomycin and also reported its utility in MDR E. coli. 5,37,38,57 Studies across different countries shows nearly 85-100% susceptibility to fosfomycin and minimal propensity for collateral damage. 14,40,41,58 In our series, we found 100% sensitivity for fosfomycin due to this drug not being in common therapeutic use.…”
Section: Discussionmentioning
confidence: 99%